Racial/Ethnic Disparities in Dental Service Utilization for Foreign-Born and U.S.-Born Middle-Aged and Older Adults. (October 2019) - Zhang, Wei; Wu, Yan Yan; Wu, Bei
This study examines racial/ethnic disparities of dental service utilization for foreign-born and U.S.-born dentate residents aged 50 years and older. Generalized linear mixed-effects models (GLMM) were used to perform longitudinal analyses of five-wave data of dental service utilization from the Health and Retirement Study (HRS). We used stratified analyses for the foreign-born and U.S.-born and assessed the nonlinear trend in rates of dental service utilization for different racial/ethnic groups. Findings indicate that Whites had higher rates of service utilization than Blacks and Hispanics regardless of birthplace. For all groups, the rates of service utilization decreased around age 80, and the rates of decline for Whites were slower than others. The U.S.-born showed the trend of higher rates of service utilization than the foreign-born for all racial/ethnic groups. These findings suggest the importance of developing culturally competent programs to meet the dental needs of the increasingly diverse populations in the United States.